2018
DOI: 10.1029/2018gc007448
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Evidence for Large‐Scale Drainage Reorganization in Northwest Africa During the Cretaceous

Abstract: West African drainage reorganization during Cretaceous opening of the Atlantic Ocean is deciphered here from geochemical provenance studies of Central Atlantic sediments. Changes in the geochemical signature of marine sediments are reflected in major and trace element concentrations and strontium‐neodymium radiogenic isotopic compositions of Cretaceous sedimentary rocks from eight Deep Sea Drilling Project (DSDP) sites and one exploration well. Homogeneous major and trace element compositions over time indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 127 publications
2
19
0
Order By: Relevance
“…Canyons and associated erosion at this stratigraphic level extend beyond the limit of the study area (Figure 1), as indicated to the north (Martin et al, 2010) and south Mourlot, Roddaz, et al, 2018). Mounded interfluves are preserved, with the largest having a maximum area of ca.…”
Section: Quantitative Seismic Geomorphologymentioning
confidence: 62%
See 2 more Smart Citations
“…Canyons and associated erosion at this stratigraphic level extend beyond the limit of the study area (Figure 1), as indicated to the north (Martin et al, 2010) and south Mourlot, Roddaz, et al, 2018). Mounded interfluves are preserved, with the largest having a maximum area of ca.…”
Section: Quantitative Seismic Geomorphologymentioning
confidence: 62%
“…This regional, extra-basinal, siliciclasticprone source of sediment and drainage is postulated to vary laterally and may have also exerted a control over the location and health of the carbonate factories and accumulation of the platform along this mixed-system margin. , Mourlot, Roddaz, et al (2018) show multiple entry points for similar-aged deltaic systems (see their Figure 9b), introducing a regional source of sediment from rivers draining the onshore Senegal Basin and hinterland of northwest Africa. This sediment is likely to be very different in composition to locally derived material associated with the erosion and collapse of the margin.…”
Section: Sediment Transfer From Shelf To Basinmentioning
confidence: 96%
See 1 more Smart Citation
“…Sediment provenance analysis conducted in Morocco and surroundings are scarce. Five recent works investigated the provenance with detrital zircon U-Pb (Azdimousa et al, 2019;Domènech et al, 2018;Marzoli et al, 2017;Pratt et al, 2015;Perez et al, 2019); one study used traced elements and radiogenic Nd-Sr isotopes (Ali et al, 2014), one using neodymium isotopes and major/trace elements from DSDP wells (Mourlot et al, 2018), and one produced detrital LTT ages (Sehrt, 2014). Several studies have also documented palaeocurrent directions in fluvial systems (e.g.…”
Section: Sands Mapmentioning
confidence: 99%
“…Pratt et al (2015) collected Albian sediments deposited in the Rif basin, and traced the provenance to two sources: the Meseta and another unknown area. Finally, Mourlot et al, (2018) undertook a largescale provenance study targeting Albian to Maastrichtian sediments from DSDP wells (from north to south offshore Morocco sites 370, 416, 415 and 369 were sampled) along the NW African coast. They used the major and trace element concentrations from these marine sediments, as well as Nd isotopes, to constrain continental crust signatures.…”
Section: Late Post-rift and Atlas Orogeny: Middle Cretaceous To Neomentioning
confidence: 99%